1997
DOI: 10.1108/02686909710180698
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking in accounting education: processes, skills and applications

Abstract: Explains that many prestigious bodies, including the American Assembly of Collegiate Schools of Business and the Accounting Change Commission, have asked accounting educators to improve their students’ critical thinking skills. Suggests that the literature contains few examples of how to apply such skills in an accounting environment and how to teach such skills as efficiently as possible. Explains and provides examples of such critical thinking skills. Shows how to incorporate such skills in the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Problem solving and critical thinking are integrated into taxation (Kimmel, 1995;Reinstein & Bayou, 1997); teamwork skills, particularly involving consulting projects, are incorporated into accounting information systems (Bryant, 2001;Sheets & Johnson, 2008); and written and oral communication assignments are embedded into introductory accounting courses (Dudley, Davis, & McGrady, 2001;Kerby & Romine, 2009). …”
Section: Common Threads Binding the Accounting Capstone: Links To Thementioning
confidence: 99%
“…Problem solving and critical thinking are integrated into taxation (Kimmel, 1995;Reinstein & Bayou, 1997); teamwork skills, particularly involving consulting projects, are incorporated into accounting information systems (Bryant, 2001;Sheets & Johnson, 2008); and written and oral communication assignments are embedded into introductory accounting courses (Dudley, Davis, & McGrady, 2001;Kerby & Romine, 2009). …”
Section: Common Threads Binding the Accounting Capstone: Links To Thementioning
confidence: 99%
“…The academy and other relevant institutions have not remained crystallized. For instance, Bordage, Foley and Goldyn [6], identified desirable skills and attributes for future educational programmes of health care Directors; Reinstein and Bayou [29] argue that the teaching of accounting must adapt to the new reality, giving their students requirements to think critically. Elmore [11] criticises the inability of the American education system and its leaders to respond to new requirements.…”
Section: St Century Skillsmentioning
confidence: 99%
“…Critical thinking has many definitions (Reinstein and Bayou, 1997). Baril et al (1998) pointed out that there was no universally accepted definition of critical thinking because of the difficulty in observing and evaluating mental processes, and the fact that "thinking" was an integral part of mental behaviour such as problem recognition, problem solving, and the exercise of judgment.…”
Section: Higher-order Thinking Skills (Hots)/ Critical Thinkingmentioning
confidence: 99%
“…These require the application of assumptions, knowledge, competence and the ability to challenge one's own thinking. Reinstein and Bayou (1997) used the definition of critical as that given in the American Heritage Dictionary as "characterised by careful and exact evaluation and judgment". They concluded that critical thinking focused on problem identification and problem solving; it was a rational response to questions that could not be answered definitively and for which relevant information was not readily available.…”
Section: Higher-order Thinking Skills (Hots)/ Critical Thinkingmentioning
confidence: 99%
See 1 more Smart Citation